Design Theory Methods and Organization for Innovation - Le Masson, Pascal; Weil, Benoit; Hatchuel, Armand; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This textbook presents the core of recent advances in design theory and its implications for design methods and design organization. Providing a unified perspective on different design methods and approaches, from the most classic (systematic design) to the most advanced (C-K theory), it offers a unique and integrated presentation of traditional and contemporary theories in the field. Examining the principles of each theory, this guide utilizes numerous real life industrial applications, with clear links to engineering design, industrial design, management, economics, psychology and creativity. Containing a section of exams with detailed answers, it is useful for courses in design theory, engineering design and advanced innovation management. "Students and professors, practitioners and researchers in diverse disciplines, interested in design, will find in this book a rich and vital source for studying fundamental design methods and toolsas well as the most advanced design theories that work in practice". Professor Yoram Reich, Tel Aviv University, Editor-in-Chief, Research In Engineering Design. Twenty years of research in design theory and engineering have shown that training in creative design is indeed possible and offers remarkably operational methods - this book is indispensable for all leaders and practitioners who wish to strengthen theinnovation capacity of their company. Pascal Daloz Executive Vice President Dassault Systèmes.
Introductory chapter: Canonical model of design regimes -- Chapter 1: Designing in a rule-based regime - systematic design theory and project management -- Chapter 2: Designing the rules for rule-based design - conceptual and generative models, axiomatic design theory -- Chapter 3: Designing in an innovative design regime - introduction to C-K design theory -- Chapter 4: Designing the innovative design regime - C-K based organisations -- Appendices: Annals of exams (8 exams, 5 with detailed answers).
Keywords: Engineering design; Computer-aided engineering; Technological innovations; Psychology, Industrial; Engineering Design; Computer-Aided Engineering (CAD, CAE) and Design; Innovation and Technology Management; Work and Organizational Psychology